Lysophosphatidylcholine Decreases the Synthesis of Tissue Factor Pathway Inhibitor in Human Umbilical Vein Endothelial Cells - Sato, Naoaki; Kokame, Koichi; Miyata, Toshiyuki; Kato, Hisao (Thrombosis and Haemostasis, 1998)
Thrombotic complications are frequently associated with atherosclerosis. Lysophosphatidylcholine (LPC), a component accumulated in oxidatively modified LDL (ox-LDL), is known to play a crucial role in the initiation and progression of atherosclerotic vascular lesions. Since a vascular anticoagulant, tissue factor pathway inhibitor (TFPI), has the function of regulating the initial reaction of tissue factor (TF)-induced coagulation, we investigated the effect of LPC on TFPI synthesis in cultured human umbilical vein endothelial cells (HUVEC). The treatment of HUVEC with LPC for 24 h decreased TFPI antigen levels in both the culture medium and the cell lysate in a dose-dependent manner. Northern blot analysis revealed that LPC caused a time-dependent decrease in the TFPI mRNA levels. The levels of TFPI antigen and mRNA were decreased to 72% and 38%, respectively, by the incubation with 50 μM LPC for 24 h. The down-regulation by LPC of TFPI mRNA expression was not observed in the presence of cycloheximide, suggesting that protein synthesis was involved in the suppression of TFPI mRNA expression. The TFPI mRNA levels in actinomycin D-treated cells were relatively stable, indicating that the down-regulation of TFPI mRNA by LPC would be partly explained by the enhanced mRNA destabilization. In contrast to the significant down-regulatory effects of LPC on TFPI expression, LPC did not induce TF mRNA expression in HUVEC. These results indicate that LPC accumulated in the atherosclerotic vascular wall would suppress endothelial TFPI synthesis, reducing the antithrombotic property of endothelial cells.